Errata: New measures of graph irregularity - Clive Elphick; Pawel Wocjan (Electronic Journal of Graph Theory and Applications, 2015)
This paper gives an errata to the paper "New measure of graph irregularity", Electronic Journal of Graph Theory and Applications {\bf 2}(1) (2014), 52-65.